Defining the energy properties of CdI2 film by experimental and theoretical methods - Solovyov, Mykola; Semkiv, Ihor; Kashuba, Andrii (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the compound CdI2, which is actively used as a component in scintillation detectors for the detection of alpha-particle radiation. The research addresses the task to correlate experimental results with theoretically determined parameters of CdI2 films. One of the primary objectives for studying this compound is to determine its electronic structure and optical properties. The CdI2 thick film was obtained by cleaving from a bulk sample. The average thickness of the CdI2 thick film is 2 μm. The optical properties of CdI2 thick film were investigated by optical absorption spectra. The absorption spectrum fitting method was applied to estimate the optical band gap and Urbach energy of the CdI2 thick film. This method requires only the measurement of the absorbance spectrum, and no additional information, such as the film thickness or reflectance spectra. The optical band gaps and Urbach energy obtained for the CdI2 thick film are 3.05 eV and 5.17 eV, respectively. Electronic band structure and energy properties were studied for CdI2. We calculated the electron dispersion at high symmetry directions of the Brillouin zone and density of electron estimated with the generalized gradient approximation (GGA). A Perdew–Burke–Ernzerhof functional for solids (PBEsol) was applied. Based on the dispersion of energy bands, the predominant type of conductivity in the studied materials was determined. Consistency of theoretical and experimental parameters exceeds that reported in previous studies, which supports the use of CdI2 as a model compound, especially in the search and design of novel crystalline materials. The established parameters could be used in the development of components for a scintillation detector